Fleet Management of Public Transportation using Internet of Things - Eswar, Moka; Titus Manohar, A; Mani, Akshay (International Journal of Engineering and Technology, 2018)
With the increase in the number of public and private buses in cities in recent years, managing the bus fleet across various routes in an efficient and effective manner has become cumbersome. This is resulting in suboptimal services, inability to effectively cater to existing demand, and poor quality of public transport services. Modern technological advancements have created a tremendous opportunity to improve various aspects of public transport services, to not only serve existing demand but attract increasing number of passengers to public transport from a sustainable development standpoint. One such area which is gaining momentum is intelligent fleet management using the concept of Internet of Things (IoT). This area calls for a cross-field collaboration between engineers from various disciplines to use the up and coming idea of Internet of Things (IoT) for overcoming the challenges of intelligent fleet management. This paper explores the opportunity for incorporation of IoT to manage bus fleets based on the occupancy ratio and the resulting benefits that can be achieved in terms of fleet frequency optimization.